1988
DOI: 10.1007/bf03179513
|View full text |Cite
|
Sign up to set email alerts
|

Probable endocrine role of midgut tissue in stimulation of digestive enzyme secretion inOryctes rhinoceros (Coleoptera: Scarabaeidae)

Abstract: The effect of midgut epithelial extract on digestive enzyme secretion in the third instar larva of Oryctes rhinoceros was studied. Midguts dissected out from third instar larvae were cut at both ends, emptied of their contents, washed in insect saline, ligated at the open ends and incubated in a medium containing extract of 2 midgut epithelia/lO ml incubation solution. In control experiments midgut preparations were incubated in insect saline without midgut epithelial extract. After 30 min of incubation, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…These results are consistent with an earlier study that showed that an increase in brain extract concentration caused an increase in the release of α-amylase from the midgut tissue of larvae of O. arenosella (Harshini et al 2003). Another study showed that a midgut peptide or probably hormone has a similar action in the larvae of Oryctes rhinoceros (Coleoptera: Scarabaeidae) (Sreekumar and Prabhu 1988).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with an earlier study that showed that an increase in brain extract concentration caused an increase in the release of α-amylase from the midgut tissue of larvae of O. arenosella (Harshini et al 2003). Another study showed that a midgut peptide or probably hormone has a similar action in the larvae of Oryctes rhinoceros (Coleoptera: Scarabaeidae) (Sreekumar and Prabhu 1988).…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, in larval corn earworms, Heliothis zed, feeding evokes an increase in FMRFamide immunoreactivity in the endocrine cells, whereas the blood concentration of the immunoreactive agent is higher in starved insects [48]. Under in vitro conditions, midgut extracts were shown to stimulate activity of digestive enzymes [49]. Our present finding of PTTH-, ATH-, and DH-like immunoreactivity in the midgut ( Table 4) indicates that the gut may exert some adenotropic effects and regulate excretion.…”
Section: Discussionmentioning
confidence: 92%